Results on Atlantic mackerel Spanish Discard Sampling Programme - Pérez-Contreras, María Nélida (2014)
Quarterly discards per ICES Divisions estimates for the Spanish bottom otter trawl fleet fishing in the Northeast Atlantic ICES Subareas VI, VII, VIII and IX are presented for Atlantic mackerel (Scomber scombrus). Information was obtained by observers on board under DCF discard sampling program carried out by the Spanish research institute IEO. Raising based on effort (number of trips) was used to estimate discards in weight and number for the most important fleets of Bottom Otter Trawlers. Discards age distributions are also presented. No trend is observed in discards volume only a great seasonality with higher discards values generally in the 1st and 4th quarter in Subarea VI_VII, and in the 1º in VIIIc and IXa Divisions. Thus, discards are highly variable throughout the series, both in weight and in number ranging from 30 to 4 580 tonnes per quarter and from 2 to 70 million fish. The highest discard weights are in Divisions VIIj, VIIIc and IXaN. 100% catches are discarded in Sub-areas VI-VII. Ages modes can, to some extent, be followed from one quarter to the next, especially in Divisions VIIIc-IXaN, although the signal is not very strong.